(untitled) (Quest Journal of Management and Social Sciences, 2020)
Background: Remittance remains a key source of external resource flows for developing countries. Remittance inflows are the addition of migrant remittance inflow and compensation of employees which include current transfers by migrant workers, with wages and salaries earned by non-resident workers. Remittance is an essential aspect of leveraging remittance to promote economic development. In the context of Nepal, remittance recipient households tend to spend more on consumption, health and education as compared to remittance non-receiving households. Objective: This study examines the impact of remittances on the consumption and investment in the context of province five of Nepal. Methods: This study is based on primary sources of data with 570 observations. The primary survey was used to extract the information from the respondents regarding the remittance amount, consumption and investment of individual household from the families of Rupandehi, Dang and Rolpa districts of Nepal whose family member has been working out of country. The regression models are estimated to test the significance and impact of remittances on the investment and consumption. Consumption and investment are the dependent variables. The independent variables are remittance, annual domestic income, household size, family residential area and level of education. Results: The results show that there is a positive relationship between remittances and consumption. This indicates that higher the amount of money inflow as a remittance, higher would be the consumption. Similarly, there is positive relationship domestic income and consumption which indicates that higher the level of domestic income, higher would be the consumption. Likewise, there is a positive relationship between household size and consumption. It indicates that larger the members in a family, higher would be the consumption. The result also reveals that there is a positive relationship between level of education and consumption. It indicates that higher the level of education, higher would be the consumption. Conclusion: Remittance has been leading to the consumption and investment behavior of rural household in province five. Remittance followed by family size is the most influencing factors that explain the changes in consumption and investment of families in province five of Nepal. Implication: This study can be useful to concerned authorities for further planning of proper investment of remittance.